Pengaruh Volatilitas Nilai Tukar terhadap Volume Perdagangan Internasional di ASEAN-3 - Fatimatuz Zahroh; Z. Zainuri; Rafael Purtomo (UPT Penerbitan Universitas Jember, 2019)
This study aims to determine the effect of exchange rate volatility on export demand in ASEAN 3 countries namely Indonesia, Thailand and the Philippines. In this research use Error Correction Model (ECM) Domawitz-Elbadawi method to know how dependent variable influence to independent variable in short term and in long term. The data used in this study is secondary data covering data exchange rate, CPI (Consumer Price Index), FDI (Foreig Direct Investment) and Export from 1997Q1- 2016Q3. The results show that in the short run the exchange rate volatility has a negative and significant effect on export demand in the country of Indonesia while for the Philippines and Thailand the exchange rate volatility has a negative but insignificant effect. In the long term, exchange rate volatility has negative but not significant effect on export demand in Indonesia and Thailand, while in Philippine, exchange rate volatility has positive and significant effect on export demand. It shows the importance of exchange rate policy in improving Indonesia’s export performance. Keywords: Exchangerate, Export, and ECM) Domawitz-Elbadawi.